Volatility modeling in the Peruvian stock market - Abanto Valle, Carlos (2007)
This article begins with an introduction to the literature on time-varying volatility models and briefly addresses the Bayesian implementation of the ARCH/GARCH/EGARCH class of models. Likewise, an application using the return series of the Return Index of the Lima Stock Exchange (IBVL) is presented and, finally, different specifications of the GARCH/EGARCH class of models are compared using the DIC criterion.